Identification of SCAR markers for genetic authentication of Dendrobium nobile Lindl. - H. Deng; M.A. Khan; X. Liu; J. Fu; Z. Mei (Brazilian Journal of Biology, 2022)
Abstract Dendrobium nobile Lindl. is an orcid plant with important medicinal values. This is a colourful houseplant, and also a popular herb in traditional Chinese medicine (TCM). The variants of this plant from different geographic regions might be high, and in this study, we aimed to develop specific sequence characterized amplified region (SCAR) markers for the identification of specific variant of this plant. Different cultivars of D. nobile were collected from nine different places of China, and one cultivar from Myanmar. DNA materials were extracted from the plant samples, random amplified polymorphic DNA (RAPD) were developed, cloned and sequenced for the development of SCAR markers. We have developed four SCAR markers, which are specific to the cultivar from Luzhou China, and clearly distinguishable (genetically) from other cultivars. These SCAR markers are deposited in GenBank (accession number MZ417502, MZ484089, MZ417504 and MZ417505). Four SCAR markers for D. nobile are effective molecular technique to genetically identify the different cultivars or species, and this method is applicable for genetic characterization and identification of other plant species too.